Teaching pronouns in classes of Portuguese as an additional language: further discussions - Andrighetti, Graziela; Perna, Cristina (BELT - Brazilian English Language Teaching Journal, 2016)
This article aims to propose reflections on pedagogical practices for Portuguese as Additional Language (PAL) involving the teaching of pronouns. Assuming that learning a language is learning to use it to (inter) act with different purposes and interlocutors (Clark, 2000), and that language is identity, built on a daily basis in several oral and written practices (Marcuschi, 2008), we seek to observe how the teaching of pronouns is proposed in textbooks of PAL and how these activities promote reflections on gender pronouns and the relations that are established among these uses and identity papers assumed by the speakers of a language in specific contexts of communication. The analysis of teaching materials points to a work with pronouns that is still limited to an approach to lexico-grammatical aspects of the language as a code, not including cultural relations, feeling of belonging, of assumed roles that are established from their use in social practices. Finally, we present a pedagogical task focused on the teaching of pronouns, to contribute to the teaching of PLA from a conception of language in use.